2019
DOI: 10.5194/acp-19-14621-2019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of convectively lofted ice on the seasonal cycle of water vapor in the tropical tropopause layer

Abstract: Abstract. We use a forward Lagrangian trajectory model to diagnose mechanisms that produce the water vapor seasonal cycle observed by the Microwave Limb Sounder (MLS) and reproduced by the Goddard Earth Observing System Chemistry-Climate Model (GEOSCCM) in the tropical tropopause layer (TTL). We confirm in both the MLS and GEOSCCM that the seasonal cycle of water vapor entering the stratosphere is primarily determined by the seasonal cycle of TTL temperatures. However, we find that the seasonal cycle of temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 76 publications
2
19
2
Order By: Relevance
“…The same global-model convective ice product was used by Dessler et al (2016) to show that convective ice sublimation has an important contribution to model-predicted future trends in stratospheric humidity. The Wang et al (2019) analysis indicated that the convective hydration in their model was primarily occurring over the ASM, which contradicts the available observational evidence presented here and in previous studies. This inconsistency between the model results and observations attests to the importance of accurately representing the distribution of convective ice relative to the tropopause for estimation of lower stratospheric hydration in models.…”
Section: Journal Of Geophysical Research: Atmospherescontrasting
confidence: 88%
See 1 more Smart Citation
“…The same global-model convective ice product was used by Dessler et al (2016) to show that convective ice sublimation has an important contribution to model-predicted future trends in stratospheric humidity. The Wang et al (2019) analysis indicated that the convective hydration in their model was primarily occurring over the ASM, which contradicts the available observational evidence presented here and in previous studies. This inconsistency between the model results and observations attests to the importance of accurately representing the distribution of convective ice relative to the tropopause for estimation of lower stratospheric hydration in models.…”
Section: Journal Of Geophysical Research: Atmospherescontrasting
confidence: 88%
“…This inconsistency between the model results and observations attests to the importance of accurately representing the distribution of convective ice relative to the tropopause for estimation of lower stratospheric hydration in models. Convective clouds in most global models, including the one used by Wang et al (2019), are generated by convective parameterizations, with large uncertainties for even moderately strong convection and even larger uncertainties for the extreme outlier systems reaching the tropopause and beyond.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…Compared to other processes, VMIX shows a weak increase of water vapour in the AMA related to the enhanced tropospheric mixing, including turbulence and convective updrafts. Apparently, this is not consistent with Ueyama et al (2018); Wang et al (2019) that highlight the importance of convection to reproduce the monsoonal maxima of water vapour. However, it is highly likely that the effect of convective updrafts is very limited by the filtering of air parcels below 250 hPa in our LTF set-up.…”
Section: Lower Stratospheric Water Vapour Distributionscontrasting
confidence: 61%
“…To create a common framework between previous studies focusing on water vapour simulation (Schoeberl et al, 2013;Zhang et al, 2016;Wang et al, 2019) and our CLaMS sensitivity experiments, we have implemented the forward domain-filling technique, here referred as Lagrangian Trajectory Filling (LTF), into CLaMS. This set-up, described by Schoeberl and Dessler (2011), has been widely used to study different properties of water vapour in the stratosphere and UTLS region (Schoeberl et al, 2012(Schoeberl et al, , 2013(Schoeberl et al, , 2014Dessler et al, 2014;Zhang et al, 2016;Ye et al, 2018;Schoeberl et al, 2018Schoeberl et al, , 2019.…”
Section: Domain Filling Set Upmentioning
confidence: 99%
See 1 more Smart Citation